2021
DOI: 10.1111/tpj.15427
|View full text |Cite
|
Sign up to set email alerts
|

Functional modulation of an aquaporin to intensify photosynthesis and abrogate bacterial virulence in rice

Abstract: Plant aquaporins are a recently noted biological resource with a great potential to improve crop growth and defense traits. Here, we report the functional modulation of the rice (Oryza sativa) aquaporin OsPIP1;3 to enhance rice photosynthesis and grain production and to control bacterial blight and leaf streak, the most devastating worldwide bacterial diseases in the crop. We characterize OsPIP1;3 as a physiologically relevant CO 2 -transporting facilitator, which supports 30% of rice photosynthesis on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 89 publications
(147 reference statements)
1
4
0
Order By: Relevance
“…Our study finds that AtPIP1;4 and AtPIP2;4 regulate plant growth, which is similar to earlier reports [51,52]. Some plant PIPs have been proven to be efficient CO 2 transport channels, capable of promoting CO 2 transport to enhance photosynthesis, thereby facilitating growth and grain yield [11,15,25]. We have also identified the important role of AtPIP1;4 in plant growth in our previous research, where AtPIP1;4 interacts with the Hpa1 to enhance CO 2 transport, net photosynthetic rate, and mesophyll conductance, thereby promoting plant growth [51].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study finds that AtPIP1;4 and AtPIP2;4 regulate plant growth, which is similar to earlier reports [51,52]. Some plant PIPs have been proven to be efficient CO 2 transport channels, capable of promoting CO 2 transport to enhance photosynthesis, thereby facilitating growth and grain yield [11,15,25]. We have also identified the important role of AtPIP1;4 in plant growth in our previous research, where AtPIP1;4 interacts with the Hpa1 to enhance CO 2 transport, net photosynthetic rate, and mesophyll conductance, thereby promoting plant growth [51].…”
Section: Discussionsupporting
confidence: 91%
“…AQPs are integral membrane proteins initially characterized as water (H 2 O) transport channels [12]. Subsequent studies have revealed that AQPs can also transport more than 20 small molecule compounds, such as CO 2 [11,[13][14][15], H 2 O 2 [9][10][11], NH 3 [16], NO [17], and others [18,19]. Through their function in mediating substrate transport, AQPs regulate a variety of pathological and physiological processes [4,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photosynthesis stands as a fundamental and universal process that is crucial for the survival of plants, while immune defense plays a pivotal role in adapting to the growth environment. Numerous studies have underscored the intricate interconnection between these two vital processes within a complex network [37][38][39][40][41]. Secondary metabolism pathways emerge as particularly crucial in tea plant resistance to diseases.…”
Section: Discussionmentioning
confidence: 99%